2016
DOI: 10.1038/srep39477
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Silk Fibroin/Sodium Alginate Composite Scaffold for Soft Tissue Engineering

Abstract: A cytocompatible porous scaffold mimicking the properties of extracellular matrices (ECMs) has great potential in promoting cellular attachment and proliferation for tissue regeneration. A biomimetic scaffold was prepared using silk fibroin (SF)/sodium alginate (SA) in which regular and uniform pore morphology can be formed through a facile freeze-dried method. The scanning electron microscopy (SEM) studies showed the presence of interconnected pores, mostly spread over the entire scaffold with pore diameter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 46 publications
5
108
0
1
Order By: Relevance
“…Fig. This result is comparable with the studies reported by Wang et al [29] and Boateng and Areago [30]. There are different phases between scaffolds with and without the cockle shell powder.…”
Section: Characterization Of Bone Scaffoldssupporting
confidence: 91%
“…Fig. This result is comparable with the studies reported by Wang et al [29] and Boateng and Areago [30]. There are different phases between scaffolds with and without the cockle shell powder.…”
Section: Characterization Of Bone Scaffoldssupporting
confidence: 91%
“…The water stability of the scaffolds under different conditions was studied to confirm the crosslinking reaction between SF and CS. 5860 The untreated scaffolds easily dissolved in water at 37 °C, because CS and SF with a low beta sheet content are water soluble (Figure 1C). When the scaffolds were immersed in methanol without EDC for 3 h, pure CS scaffolds remained soluble in water, while the weight loss was 19%, 15%, 12%, 8% and 4% for S2-C, S4-C, S6-C, S8-C, and pure SF, respectively, because the CS was soluble after methanol treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Alginate is highly hydrophilic, biocompatible, relatively economical and biodegradable under normal physiological conditions [46]. Owing to its unique physiological properties, composite scaffolds have been found successful with alginate combined with different other biomaterials like HAp [47], chitosan [48], collagen [49] and silk fibroin [50] for bone regeneration.…”
Section: Alginatementioning
confidence: 99%